Firm and whole chain success: network management in the Ukrainian food industry - Taras Gagalyuk; Jon Henrich Hanf; Martin Hingley (Journal on Chain and Network Science, 2013)
This article develops the theoretical foundations of supply chain network management in order to investigate the constructs surrounding whole chain success rather than just success at firm level. It is argued that the `network success' link has been under-studied, with most empirical studies focusing on the achievement of goals by an individual firm in a network context. A model of the whole network's success in the context of supply chain networks in food industry supply chain relationships is used. The results identify that network-level goals must be considered alongside firm-level goals in supply chain networks. Furthermore, network-level goals are subject to the impacts of chain management and have to be of particular interest for focal firms that are responsible for the development and implementation of collective strategies.
Keywords: 330; integrated channel relationships; food